Linked Open Data native cataloguing and archival description - Daquino, Marilena (JLIS.it : Italian journal of library and information science, 2021)
In the last years cultural heritage institutions have radically changed the way they publish their data. Publishing Linked Open Data (LOD) offers many advantages, in terms of innovation, visibility, and engagement with patrons. New data are served along with legacy services and data, via dedicated interfaces that allow developers and Digital Humanists to access specialised information. However, Linked data are living entities that change over time and require expensive curatorial activities, and should not be misaligned with respect to original data. To cope with this problem, several LOD-native cataloguing systems have been created. In this article an overview of current projects for LOD-native cataloguing is provided. Projects and systems are analysed with respect to related problems and benefits. [Publisher's Text]